(untitled) (Bangladesh Journal of Agricultural Research, 2012)
The present studies were carried out to characterize seventy-one aromatic rice germplasm from IGKV, Raipur. These germplasm were characterized and grouped on the basis of anthocyanin pigmentation, plant habit, and awning character. On the basis of pigmentation distribution in 10 plant parts, a total of twelve groups were formed with group one having no pigmentation and group twelve with pigmentation in 9 plant parts. On the basis of plant habit and awning character, three groups of each were formed. The genetic parameters for the ten agronomic traits indicated that the selection of genotypes may be done for fertile spikelets per panicle, spikelet density, spikelet sterility percentage, and hundred seed weight. Thus, on the basis of above characters, the genotypes Tulsi Mala, Baanspati, Ganga Balu, Samund Chini, Tulsi Amrit, Dudh Dhan, Kari Gilas, Shankar Jeera, and Jata Shankar may be selected for future study. DOI: http://dx.doi.org/10.3329/bjar.v37i1.11168 Bangladesh J. Agril. Res. 37(1): 1-8, March 2012